2021
DOI: 10.1007/s12144-021-02345-8
|View full text |Cite
|
Sign up to set email alerts
|

Compassionate goals and responses to social rejection: A mediating role of self-compassion

Abstract: The present study examined how people with compassionate goals cope with the threat of social rejection. Specifically, we tested whether self-compassion mediates the associations between compassionate goals and adaptive responses in the wake of social rejection. Participants (n = 358) first filled out the measure of compassionate goals and then described their personal experience of being rejected by others in their life. Later, they reported their levels of self-compassionate reactions toward their experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…However, this threatavoidance behavior might generate negative affect equally for the recipient and rejector (Doolaard et al, 2020). Past research has observed negative affect among recipients (Stinson et al, 2011;Hebl et al, 2012;Li et al, 2012;Kawamoto et al, 2017;Miyagawa et al, 2021). As the symmetric party in social rejection, the emotional responses of the rejector still lack awareness from scholars.…”
Section: Social Rejection and Negative Affectmentioning
confidence: 99%
“…However, this threatavoidance behavior might generate negative affect equally for the recipient and rejector (Doolaard et al, 2020). Past research has observed negative affect among recipients (Stinson et al, 2011;Hebl et al, 2012;Li et al, 2012;Kawamoto et al, 2017;Miyagawa et al, 2021). As the symmetric party in social rejection, the emotional responses of the rejector still lack awareness from scholars.…”
Section: Social Rejection and Negative Affectmentioning
confidence: 99%
“…A series of studies have supported the beneficial effects of self-compassion. As an attitude toward oneself, self-compassion can protect self-esteem in the context of failure or social threats (Miyagawa et al, 2021). Self-compassion is also used as an effective emotion regulation strategy to regulate negative emotions and further generate positive emotions (Diedrich et al, 2014; Rao & Kemper, 2016).…”
mentioning
confidence: 99%